Semantics Perspectives On The Historical Story of Gowe Bonio Ni'owulu-Wulu at Dahadanö Gawu-Gawu Village, Gunungsitoli City - Zebua, Etikat Muliana; Daeli, Robin Motani; Harefa, Afore Tahir (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This research aims to explain the semantics meaning based on the history of Gowe Bonio Ni'owulu-wulu cultural tourism, located in Dahadanö Gawu-gawu village, Gunungsitoli City. This research uses qualitative methods to explore how the historical story of Gowe Bonio Ni'owulu-Wulu is communicated and understood by various social groups in the context of cultural tourism. Through the use of qualitative analysis methods, such as in-depth interviews, participatory observation, and document analysis, this research identifies and understands the meanings contained in the story. The results show that a language perspective in semantics can highlight local cultural values that encourage hospitality, respect and good social relations in welcoming guests.